Enhancing the Delivery of Erythropoietin and Its Variants into the Ischemic Brain - Dirk M. Hermann (The Scientific World Journal)
The hematopoietic growth factor erythropoietin (EPO) and its neuroprotective, but not hematopoietic, variants asialoEPO, carbamylated EPO (CEPO), and low sialic acid EPO (Neuro-EPO) are attractive candidates for stroke treatment. Due to their large molecular weight, these proteins enter the brain only to a minor extent when intravenously administered, which has raised the question for alternative delivery strategies, among which intranasal delivery may certainly be an attractive choice, as the review by Garcia Rodriguez and Sosa Teste in this journal points out. Before this strategy may be considered clinically applicable, however, more and, in particular, quantitative information is needed about (a) the temporospatial accumulation of EPO and its variants in the brain tissue both in animals and nonhuman primates, and (b) the accumulation of EPO and its variants in the human cerebrospinal fluid.